Long-term exposure to ambient particulate matter (PM2.5) is associated with platelet counts in adults. (September 2018) - Zhang, Zilong; Chan, Ta-Chien; Guo, Cui; Chang, Ly-yun; Lin, Changqing; Chuang, Yuan Chieh; Jiang, Wun Kai; Ho, Kin Fai; Tam, Tony; Woo, Kam S.; Lau, Alexis K.H.; Lao, Xiang Qian
Abstract: Background: The prothrombotic effects of particulate matter (PM) may underlie the association of air pollution with increased risks of cardiovascular disease. This study aimed to investigate the association between long-term exposure to PM with an aerodynamic diameter ≤2.5 μm (PM2.5 ) and platelet counts, a marker of coagulation profiles. Methods: The study participants were from a cohort consisting of 362, 396 Taiwanese adults who participated in a standard medical examination program between 2001 and 2014. Platelet counts were measured through Complete Blood Count tests. A satellite-based spatio-temporal model was used to estimate 2-year average ambient PM2.5 concentration at each participant's address. Mixed-effects linear regression models were used to investigate the association between PM2.5 exposure and platelet counts. Results: This analysis included 175, 959 men with 396, 248 observations and 186, 437 women with 397, 877 observations. Every 10-μg/m 3 increment in the 2-year average PM2.5 was associated with increases of 0.42% (95% CI: 0.38%, 0.47%) and 0.49% (95% CI: 0.44%, 0.54%) in platelet counts in men and women, respectively. A series of sensitivity analyses, including an analysis in participants free of cardiometabolic disorders, confirmed the robustness of the observed associations. Baseline data analyses showed that every 10-μg/m 3 increment in PM2.5 was associated with higher risk of 17% and 14% of having elevated platelet counts (≥90th percentile) in men and women, respectively. Conclusions: Long-term exposure to PM2.5 appears to be associated with increased platelet counts, indicating potential adverse effects on blood coagulability. Graphical abstract: Image 1 Highlights: Long-term exposure to PM2.5 is associated with increased platelet counts. Long-term exposure to PM2.5 is associated with an increased risk of having an elevated platelet count. PM-induced increases in platelet may serve as a potential mechanism linking PM air pollution with cardiovascular disease.